THE INFLUENCE OF EUROPEAN CONVENTION FOR THE PROTECTION ON HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS UPON ROMANIAN SUCCESIONAL LAW RELATIONS - Gelei, Ioana (European Scientific Journal, ESJ, 2013)
The paper is reviewing the influence of European Convention on Human Rights upon Romanian succesional law from several terms or ways of : This one is reviewed in term of principles of rule of law and subsidiarity, two important principles in European Protection of Human Rights Law , the first one being close connected to rule of law state and authentic democracy and the second one being close connected to state’s involvement in legislative cadre of human rights creation and their respect’s controle, in term of right to respect private and family life, a conditional and interdependent with liberalities and legal and testamentary successions matter right and in term of protection of property , which is including the general principle of right of property ’s respect , a real principal right. This one is reviewed by way of right to marry, which means also right to marry for that matter and to found a family of man and woman which have legal age , by way of equality between spouses , which is gathering way in civil rights and obligations field and by way of general principle of prohibition of discrimination, an european and international principle, too. The paper is studying the relations between national law and european human rights protection law, a matter mainly regulated in internal law by Romanian Constitution and res interpretata of European Court of Human Rights decisions , which are producing in that term effects erga omnes. We are suggesting the amendment of European Convention on Human Rights by an Additional Protocol, which is regulating the right to inherit of persons , as a human and a civil right, too